An Analysis Of Warning Utterances In Al-Qur'an English Translation Of Ibn Kathir Interpretation - Muliawan, Anugrah Adi (2012)
This research deals with warning utterance in Al-Quran English translation of Ibn Kathir Interpretation. The aims of the research are identifying the reconstructed syntactical forms and describing the utterance meaning in Al-Quran English translation of Ibn Kathir Interpretation . The type of this research is qualitative study. This research has data source from Al-Quran English translation of Ibn Kathir Interpretation chapter al-Mulk.The technique of collecting data is documentation and the steps are classifying, and taking the data. The technique of analyzing data is classiflying describtive technique. The way is to identifying the reconstructed forms of warning utterance in Al-Quran English translation of Ibn Kathir Interpretation by applying the syntactic forms theory by Frank and describing the meaning of warning utterance in Al-Quran English translation of Ibn Kathir Interpretation by applying John Lyon theory. This research shows that : (1) There are two syntactic form in Al-Quran English translation of Ibn Kathir Interpretation chapter Al-Mulk. There are; (a) declarative sentence (91,30%) and (b) interrogative sentence (8,70%). (2) There are four types of utterance meaning in Al-Quran English translation of Ibn Kathir Interpretation chapter Al-Mulk: There are ; (a) warning by threat (26,20%), (b) warning by information (26,20%), (c) warning by motivation (8,40%) (d) warning by reflection (39,20%).